Deviations in Circulating TNFα Levels and TNFα Production by Mononuclear Cells in Healthy Human Populations - T. Mózes; I. Baráth; K. Gornicsar; A. Grosz; Ta. Mózes; Cs. Göndöcs; P. Széphalmi; K. Gaál; E. Madarász (Mediators of Inflammation)
Objectives. Tumor necrosis factor alpha (TNFα) plays a pivotal role in the inflammatory host response. The serum-level of TNFα and the production of TNFα by lympho/monocytes, however, seem to show high individual variations. The goal of the present study was to investigate the variations and inducibility of TNFα-activity in two age-groups of healthy volunteers. Methods. Sixty elderly, healthy volunteers were studied. These persons were free of malignant diseases, and within three months, they did not have any trauma or inflammatory disease and were not taking any steroids or nonsteroid anti-inflammatory drugs. Thirty young volunteers were also included. Blood samples were taken; lympho/monocytes were separated and cultured with or without endotoxin (LPS) stimulation. Serum and culture supernatant TNFα levels were determined by bioassay using WEHI 164 cells. Results. The results indicated significant individual variations in TNFα levels of healthy volunteers irrespective of age. Subgroups with low, middle, and high serum TNF-levels were distinguished. In about 50% of volunteers with low serum-TNFα activity, LPS stimulation failed to increase the TNFα production by isolated lympho/monocytes. Conclusion. Our data suggest a chance to select individuals with enhanced sensitivity for septic complications.